Meat Quality of Rainbow Trout (Oncorhynchus Mykiss) from the Bistrișorii Valley Trout Farm, Alba County - Andrada IHUŢ; Camelia RĂDUCU; Daniel COCAN; Călin LAȚIU; Paul UIUIU; Vioara MIREŞAN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2018)
Fish meat represents a great energy source in human nutrition, due to its content in high biological value protein, lipids which contain omega acids and minerals. The chemical composition of fish meat can be influenced by several factors such as: species, administered feed, environment, age and spawning period. The aim of this research was to analyse the chemical composition of the rainbow trout meat reared in the fishery Valea Bistrişorii, in a classical system. The determination of water (W %), minerals (M %) and dry matter (DM %) content was performed by calcination. The crude fat (CF %) was determined by Soxhlet method and crude protein (CP %) by the Kjeldahl method. Analysing the chemical composition of the rainbow trout meat, the following values were obtained: W = 73.60 ± 0.23%; DM = 26.40 ± 0.14%; CP = 18.21 ± 0.14%; CF = 6.87%; M = 1.32%.The obtained data offers useful information of meat chemical composition for selection of future breeders and improving the rainbow troutraised in the Bistrişorii Valley.